1994
DOI: 10.1007/bf02409399
|View full text |Cite
|
Sign up to set email alerts
|

Parallel counter implementation

Abstract: Abstract. An (n, m) parallel counter is a circuit with n inputs that produces an m-bit binary count of the number of its inputs that are ONEs. This article reports on the design of large parallel counters with up to 1023 inputs. Design trade-offs are examined regarding the use of counter cells of size ranging from (3,2) to (31,5) as building blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…In successive doubling approach, full adders are used to implement the counters. The synthesized counters are manually optimized [5] or obtained by computer-aided design [6]. These counters have lesser delay but higher hardware complexity than the full adder based counters.…”
Section: Analysis Of Existing Countersmentioning
confidence: 99%
See 2 more Smart Citations
“…In successive doubling approach, full adders are used to implement the counters. The synthesized counters are manually optimized [5] or obtained by computer-aided design [6]. These counters have lesser delay but higher hardware complexity than the full adder based counters.…”
Section: Analysis Of Existing Countersmentioning
confidence: 99%
“…The switching tree counters shown in [3] are implemented using relay switches but the complexity of this approach grows as the square of the number of inputs. The most popular and widely used existing counters are successive doubling counters [4] and synthesized counters [5,6]. In successive doubling approach, full adders are used to implement the counters.…”
Section: Analysis Of Existing Countersmentioning
confidence: 99%
See 1 more Smart Citation
“…In [1] Jones and Swartzlander have compared the design of parallel counters using only (3,2) or (2,2) counters to designs using more complex counters like (7,3), (15,4) and (31,5). They have analyzed the delay and area of different implementations and concluded that designs based on (3,2) and (2,2) counters only are generally superior.…”
Section: Saturating Counters -Design Alternativesmentioning
confidence: 99%
“…Various designs of parallel counters to be used in multiplier units and other applications have been proposed and implemented (e.g., [1,2]). Such designs use different basic building blocks like (3,2) counters, (7,3) counters and the like [3].…”
Section: Introductionmentioning
confidence: 99%